SUPER BROTAMENTO DO GUARANAZEIRO (Paullinia cupana H.B.K. var. sorbilis (Mart.)Ducke) NO ESTADO DE SÃO PAULO - Feitosa, Maria Imaculada; Pimentel, Cybelle Pacheco Vaz; Oliveira, Victor Paulo de; Boaventura, Marco Antônio M. (REVISTA DE AGRICULTURA, 2015)
SUPER BROTAMENTO DO GUARANAZEIRO (Paullinia cupana H.B.K. var. sorbilis (Mart.)Ducke) NO ESTADO DE SÃO PAULO